Development of Professional Competence of Future Pedagogy and Psychology Specialists - Sansysbayeva , Dinara; Tursunai , Ibragimova; Laura , Bissenbayeva; Yergeshov , Yerzhan (Journal of Ecohumanism, 2024)
The development of professional competence is essential for future pedagogy and psychology specialists to effectively meet the demands of a rapidly evolving educational and psychological landscape. Professional competence encompasses the integration of knowledge, skills, and attitudes necessary for professionals to perform their roles effectively. This research investigates the factors influencing the development of professional competence in future pedagogy and psychology specialists, focusing on curriculum design, teaching methods, practical experience, and ongoing professional development. The study employs a mixed-methods approach, combining qualitative interviews and focus groups with quantitative surveys to explore the perspectives of faculty, students, and program directors. Qualitative data will be analyzed using thematic analysis to identify common themes regarding the effectiveness of current pedagogical strategies, while quantitative data will provide insights into students' self-assessments and the perceived value of competencies like critical thinking, communication skills, and ethical reasoning. The findings are expected to highlight key competencies that future specialists need to cultivate and offer recommendations for improving educational frameworks. This study will also emphasize the importance of practical experience, such as internships and fieldwork placements, in bridging the gap between theoretical knowledge and real-world application. The research aims to contribute to the development of a comprehensive model for enhancing professional competence in pedagogy and psychology programs and provide actionable recommendations for educators and policymakers. Ultimately, this research will contribute to preparing future specialists who are not only knowledgeable but also adaptable, reflective, and ethically grounded in their professional practice.